СУБ’ЄКТИВНА СТОРОНА ПОРУШЕННЯ ВИМОГ ЩОДО ЗАПОБІГАННЯ ТА ВРЕГУЛЮВАННЯ КОНФЛІКТУ ІНТЕРЕСІВ - Загорська, Ольга Ігорівна (SUPREMANCE OF LAW, 2019)
The article explores the peculiarities of the subjective side of the offense under Article 172-7 of the Code of Administrative Offenses. The problems of establishing conflict of interests in the activities of persons authorized to perform the functions of the state and local self-government, equal to them, are covered. The legal framework regulating the subject of the research is analyzed, as well as the judicial practice that has emerged in the process of law enforcement, resulting in the gaps in the legislation in this field.